Quality of polarization entanglement in spontaneous parametric down conversion - Ali, Norshamsuri; Soekardjo, Suryadi; Saharudin, Suhairi; Wahiddin, Mohamed Ridza (EDP Sciences, 2017)
We experimentally demonstrated a high degree of polarization entanglement known as entanglement visibility through spontaneous parametric down conversion process pumped by a femtosecond laser. The entangled-photon pair was obtained using two type-I BBO crystal. The down-converted photons from these crystals demonstrates a high visibility of 98.7% (θ2 = 0°) and 90% (θ2 = 22.5°). These results are in agreement with the theory which expects high visibility from such arrangement